Implementasi Sumber Belajar Bioteknologi Berbasis Etnosains di Madrasah Ibtidaiyah Al-Munawaroh - Forniawan, Ary (Fakultas Tarbiyah dan Ilmu Keguruan UIN Jurai Siwo, Lampung, 2022)
Research objectives to determine the application of ethnoscience based biotechnology learning resources in learning and describes the implementation of the ethnoscience-based biotechnology learning process. The research method uses a qualitative descriptive research design. Subjects were 49 students of class VI Madrasah Ibtidaiyah Al-Munawaroh research object of ethnoscience-based biotechnology learning resources. data collection techniques with interviews and observation. Data analysis techniques with data collection, reduction, presentation, and conclusions. The results of data analysis showed that 49.8% of students did not understand the concept of biotechnology, the manufacturing process, the microorganisms involved, the mechanism of the fermentation process in tempe, peuyeum and bread. 100% of students know tempe, peuyeum, bread and tempe is consumed every day and the way of making it was handed down by our ancestors from generation to generation. 73% of students have not been able to provide examples of other biotechnology products and the microorganisms that play a role. Conclusion Madrasah Ibtidaiyah Al-Munawaroh has implemented ethnoscience-based biotechnology learning resources in learning but the implementation of students' ethno-science-based biotechnology learning processes is unable to explain the link between local wisdom culture and natural science.